2010
DOI: 10.3390/md8030483
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-Alkyl Pyridinium Alkaloids from the Arctic Sponge Haliclona viscosa

Abstract: 3-Alkyl pyridinium alkaloids (3-APAs) are common secondary metabolites in marine sponges of the order Haplosclerida. In recent years, our laboratory has isolated and synthesized several new members of this family such as haliclamines C–F, viscosamine, viscosaline and a cyclic monomer. All of them were isolated from the Arctic sponge Haliclona viscosa collected in Spitsbergen, Norway. In this article we report the syntheses of these secondary metabolites from Haliclona viscosa and related compounds and give a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…lendenfeldi might be related to the presence of Latrunculia -associated natural products that have already been reported to have inhibitory potential against various Gram-positive and Gram-negative bacteria, which are known as the discorhabdins [21,22,23] and trunculins [24]. Furthermore, sponges of the genus Haliclona , which also include polar species, are known to contain antibacterial 3-alkylpyridinium alkaloids [25,26]. Similarly, sesquiterpenoids halichonadins [27] and a galactoside-specific lectin [28] from Halichondria sponges have been described to have antibacterial and antifungal effects, while extracts from sponges of the genus Hemigellius have not yet been reported to show any antibiotic properties.…”
Section: Resultsmentioning
confidence: 99%
“…lendenfeldi might be related to the presence of Latrunculia -associated natural products that have already been reported to have inhibitory potential against various Gram-positive and Gram-negative bacteria, which are known as the discorhabdins [21,22,23] and trunculins [24]. Furthermore, sponges of the genus Haliclona , which also include polar species, are known to contain antibacterial 3-alkylpyridinium alkaloids [25,26]. Similarly, sesquiterpenoids halichonadins [27] and a galactoside-specific lectin [28] from Halichondria sponges have been described to have antibacterial and antifungal effects, while extracts from sponges of the genus Hemigellius have not yet been reported to show any antibiotic properties.…”
Section: Resultsmentioning
confidence: 99%
“…In 2009, new haliclamines E ( 172 ) and F ( 173 ) (Figure 17) were subsequently obtained from this Arctic sponge [96]. Compound 169 showed activity in the feeding deterrence assay against the amphipod Anonyx nugax and the starfish Asterias rubens from the North Sea [97]. Compounds 169 and 170 showed a strong inhibition against two bacterial strains isolated from the vicinity of the sponge [95,97].…”
Section: Spongesmentioning
confidence: 99%
“…Compound 169 showed activity in the feeding deterrence assay against the amphipod Anonyx nugax and the starfish Asterias rubens from the North Sea [97]. Compounds 169 and 170 showed a strong inhibition against two bacterial strains isolated from the vicinity of the sponge [95,97]. The synthesis of the Arctic sponge alkaloids were also achieved by two groups [97,98].…”
Section: Spongesmentioning
confidence: 99%
See 1 more Smart Citation
“…N-Alkyl quaternary pyridinium salts can be prepared by simple, economical and short synthetic methods. Pyridinium salts, largely of synthetic origin, and some natural products (Timm et al, 2010) have been found to show good antimicrobial activity (Obando et al, 2009;Ilangovan et al, 2012). Pyridinium succinate and acesulfamate showed good antimicrobial and insect deterrent activity (Hough-Troutman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%